Primates in reclaimed mining landscapes of South Kalimantan, Indonesia - DEDE AULIA RAHMAN; IKSAN GUSTIAWAN; MEKKA RIADHAH; RIZA NOVIAN; RANDY SAPUTRA; YUNESTO YUNESTO; JOSHUA GILBERT; HANIFULLAH HABIBIE (Society for Indonesian Biodiversity, 2026)
Abstract. Rahman DA, Gustiawan I, Riadhah M, Novian R, Saputra R, Yunesto, Gilbert J, Habibie H. 2026. Primates in reclaimed mining landscapes of South Kalimantan, Indonesia. Biodiversitas 27 (7): d270724. https://doi.org/10.13057/biodiv/d270724. Post-mining landscapes can provide secondary habitats for wildlife when ecological restoration is properly implemented. In South Kalimantan, reclamation areas within the mining concession of Perseroan Terbatas (PT) Adaro Energy Indonesia Tbk have developed into habitats utilized by several primate species, including the protected proboscis monkey and silvered langur. This study aimed to estimate the number of individuals and population density of proboscis monkeys and silvered langurs, as well as to identify strategic areas with potential for artificial canopy bridge development in the post-mining landscape of PT Adaro Indonesia. Field surveys were conducted using line transect and repeated concentration count methods during morning and afternoon observation periods across reclaimed and riparian habitats. Silvered langur abundance was estimated using distance sampling analysis, while proboscis monkey abundance was estimated through repeated concentration counts. The results recorded 10 groups of silvered langurs with an estimated abundance of 88.76 individuals and a population density of 58.16 individuals/km² distributed across five locations. Proboscis monkeys were detected primarily in riparian habitats within the Catchment of Nungkaran River area, totaling 28 individuals. The observed distribution patterns were consistent with the ecological characteristics of both species, with proboscis monkeys concentrated in riverine areas, while silvered langurs utilized a broader range of reclaimed vegetation habitats. Several strategic locations with potential for artificial canopy bridge development were also identified to improve canopy connectivity within fragmented reclaimed landscapes. These findings indicate that reclaimed vegetation and riparian corridors are utilized by protected primates in post-mining ecosystems and highlight the importance of maintaining vegetation structure and habitat connectivity in post-mining landscape management.